JUSTIFICATION FOR THE APPROACH TO THE DIFFERENT FORCES MANAGEMENT DURING THE STOPPING MASS RIOTS - Lavnichenko, Oleksandr; Chukhlatiy, Andriy (Honor and Law, 2022)
A comparison of approaches to control riots and analysis of the resolution of the Cabinet of Ministers of Ukraine were held. Some measures to be taken by the head of the operational headquarters, bodies involved in a special operation to end the riots were proposed. It is determined that in the past, in accordance with current regulations, the basis of the forces that were planned to be involved in the operation to stop the riots was a detachment. The head of the Internal Troops was only one of the deputy chiefs of the operational staff in particular for the troops, and during the violent stopping riots, his role was limited to monitoring the actions of his subordinates. It is suggested that each entity involved in the elimination of the riots should have a plan in place to mobilize forces and means to end the riots. Law enforcement agencies in the regions involved in stopping the riots must coordinate their plans with the head of the territorial department of the National Guard of Ukraine. It is determined that the level of leadership shows that this event refers at least to the emergency situation at the regional level. Accordingly, the operation to be carried out as part of measures to end the riots will be operational. It is noted that mass riots can be considered prevented if the crowd was not formed to carry out criminal intentions and if there is no threat of escalating individual conflicts into mass pogroms, destruction of property, beating people. It is considered that the decision to conduct a special operation to stop the riots is made by the head of the operational staff on the basis of analysis of the operational situation and information on entering in the Unified Register of pre-trial investigations information on criminal offenses under Article 294 of the Criminal Code. It is determined that the management of the special operation is entrusted to the operational management group. The Operational Control Group (remote point) carries out tactical control of forces and means directly in the area of the operation to stop the riots. It is noted that a special operation is carried out only when it is well prepared, which, above all, requires the necessary number of forces and means, the necessary logistics of personnel, knowledge of the composition, number and intentions of the crowd. The article does not consider approaches to preventive planning to end riots, responsibility for planning. In our opinion, it needs a separate study.